Experimental study on the quality of laser drilling in air and under water conditions - Aditya Heru Prathama (2009)
Laser drilling is commonly used for producing through-holes. From application viewpoint, producing good quality holes is the key. In this project the author investigated laser drilling on silicon wafer by trepanning both in air and under water. First, effects of variations of laser parameters on hole quality in air drilling were investigated. Second, hole quality produced by laser drilling in air and under water was compared and evaluated. A hole with excellent qualities should have minimum spatter deposition area, hole diameters, taper, and optimum circularity. Four laser parameters, namely pulse frequency (from 10 – 40 kHz), laser fluence (low and high), scanning velocities (1 – 15 mm/s), and F.P.P. (Focal Plane Position: Top and Middle) were varied. From the experimentation of air drilling, it was found that the quality of holes was better when using low pulse frequency, low laser fluence, low scanning velocity, or middle F.P.P. One benefit of laser drilling under water was that it eliminated spatter, which was commonly found in air drilling. Instead, there was formation of oxide layer. The entrance hole quality was better where the edge was sharper. In addition, the exit hole was cleaner and smoother. The better quality was due to confined plasma generated in Water Confinement Regime (WCR) which induced recoiling pressure against the material, which made ablation rate higher and more efficient. However, it was found that in water drilling, the quality of the hole was better than that resulted from air drilling only at lower scanning velocities.